Analysis of Variables Affecting The Risk of Inadequate Income in Bandarlampung City - Nansi Ria Hapsari (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
This study aims to analyze how the influence of education level, number of working hours and work experience on the risk of inadequate income (below the minimum wage) in Bandar Lampung City. The type of data used is secondary data. The types and sources of data are from the Central Bureau of Statistics (BPS) from the results of the National Labor Force Survey (SAKERNAS) in 2022. The number of eligible samples was 1,108 workers. The analytical tool used in this research is SPSS version 18. In this study, binary logistic regression analysis was used to analyze the dependent’s probability value by considering the independent variables’ fluctuation. The results show that education level and working hours are variables that significantly affect labor income in Bandarlampung City. The level of education with the largest odds ratio value is the most influential variable on labor income in Bandarlampung City